Athlete-specific optimizing simulation of armstroke in crawl swimming considering individual shoulder joint torque characteristics - Nakashima, M.; Tsuchiya, S.; Toyoda, R.; Kuramoto, A.; Koga, D.; Takagi, H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The armstroke in the crawl swimming is important since it mainly contributes to the thrust generation. The optimum armstrokes were solved by optimizing simulation for swimmers without any physical disability [1,2], with hemiplegia [3] and with unilateral transradial deficiency [4]. In those optimizing simulations, the joint torque characteristics database, which was constructed based on experiments and musculoskeletal simulation, were always used as the constraints of the optimization. However, since the joint torque characteristics vary according to individual, the optimum armstroke for each individual is also considered to vary. For this problem, a framework to solve the optimum armstroke considering athlete-specific shoulder joint torque characteristics was proposed in this study. The objective of this study was to conduct the athlete-specific optimizing simulation considering individual shoulder joint torque characteristics.